2014
DOI: 10.1055/s-0034-1394297
|View full text |Cite
|
Sign up to set email alerts
|

Neck Pain following Laminoplasty

Abstract: Study Design Retrospective evaluation of prospectively collected data. Objective To compare preoperative and postoperative neck pain following laminoplasty using the Neck Disability Index (NDI). Methods Seventy-two patients undergoing laminoplasty from 2006 to 2009 at a single institution were identified. Thirty-four patients with a minimum 1-year follow-up who completed preoperative, 6-week, and 1-year postoperative NDI questionnaires were enrolled. Demographic data and surgical data including estimated blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…[ 21 ] We retained the cervical muscle ligament complex, thus reducing the incidence of axial symptoms. [ 22 , 23 ] However, supreme mastery is needed to apply this technique to multisegmental ossification of the posterior longitudinal ligament, given the serious adhesions to the ventral surface. Also, the surgery time is longer, requiring increased patient tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] We retained the cervical muscle ligament complex, thus reducing the incidence of axial symptoms. [ 22 , 23 ] However, supreme mastery is needed to apply this technique to multisegmental ossification of the posterior longitudinal ligament, given the serious adhesions to the ventral surface. Also, the surgery time is longer, requiring increased patient tolerance.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 However, after operations a variety of symptoms remain or occur, including neck and shoulder pain, stiffness, and limited neck motion. 13 We believe that expansive open-door cervical laminoplasty creates a relative large injury and will cause damage of the ligament complex to various degrees when relaxing pressure. Because attachment relationships between posterior cervical muscular attachment points and spinous process cannot be reconstructed, posterior cervical extensors become atrophic and weak; in addition, postoperative long-time neck immobilization will cause neck symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several studies used the NDI score as a parameter of clinical outcome and reported that laminoplasty improved the NDI score within 1-2 years of post operation [39,43]. Interestingly, Shin et al [35] used the Frankel score to measure the clinical outcome of laminoplasty and found an improvement in the Frankel score from 3.93 to 4.53 at 12 months post operation.…”
Section: Clinical Outcomementioning
confidence: 99%
“…We believe that the dissection of muscular attachment at C2 and C7 is the cause of this complication; the preservation of them can reduce postoperative axial neck pain. Mesfin et al [43] demonstrated that by performing C4-C6 laminoplasty, the NDI pain subscore decreased from 1.3 to 0.7 at 1 year follow-up. The pain subscore was already low before the operation and became even lower at 1 year post operation.…”
Section: Surgical Outcomementioning
confidence: 99%
See 1 more Smart Citation